Hibridisasi pada Musik Keroncong dalam Lagu Bugih Lamo oleh Grup Orkes Keroncong Buana Lestari Sawahlunto - Ade Febri Yulfita; Asril Asril (CV. Ulil Albab Corp, 2023)
Minang pop song Bugih Lamo was composed by Syahrul Tarun Yusuf and arranged by the Buana Lestari Keroncong orchestra to become keroncong music. Bugih Lamo songs are already in the form of hybrid music between local and global cultures. The original musical arrangement uses modern musical instruments and uses diatonic tones. Keroncong music is also a hybrid music, so the two musical genres have adapted music globally following the western diatonic scale. The concept of the musical arrangement performed by the Buana Lestari Keroncong Orchestra in the Bugih Lamo song in the form of keroncong, by incorporating elements of keroncong music and other elements of Minang traditional music. The purpose of this study was to see the hybridization process in the keroncong music of the Buana Lestari Keroncong Orchestra. The method used is a qualitative method with the presentation of data is descriptive analysis. The results of this study indicate that there is hybridization and ambivalence in the arrangement of Bugih Lamo’s songs, where there is an assimilation between pop, keroncong, and traditional music. Data collection was carried out based on observation, documentation, and interviews with the artist’s work.